An efficient authoring activities infrastructure design through grid portal technology - Awang Hamid, Dayang Tiawa; Islam, Md. Rajibul; Alias, Norma; Omar, Abdul Hafidz (2010)
An authoring environment allows to built software or digital contents and an educational authoring activities infrastructure allows to create, edit and share artifacts like websites, interactive hypermedia, microworlds, simulations. This study presents an efficient authoring infrastructure dealing with online collaborative tools and collaborative authoring environment based on grid portal technology to solve the unequal distribution of task (among students in a group) and compensation (in terms of performance evaluation i.e. results in grades and positive feedback/comments from their instructors/lecturers) problem. We propose the grid portal technology to support online collaborative efforts among students on distributed parallel computing system to make it faster and efficient in order to enhance authoring support in courseware design. An open source grid portal software has used to design the authoring infrastructure along with PVM, MPI, JAVA on Linux platform. This grid poral software and the grid architecture bring computational clusters together into a grid.